DISKURSUS QIYAS NAHWI PERSPEKTIF IBN MADA DAN ABU ASWAD AD- DU’ALI - Arsyad, Hairuddin; Ramadhan, Aji Rizqi; Sopian, Asep (Universitas Islam Negeri Mataram, 2024)
There are four nahwu postulates agreed upon by the majority of ulama, namely as-sima', al-ijma', al-qiyas, and istishab al-hal. Ibn Mada and Abu Aswad Ad-Du'ali agreed on four components of Qias, namely al-asal, furu', illat, and law. However, this research aims to identify his contribution to the field of nahwi science and identify the contrasting views that occur between Ibn Mada and Abu Aswad Ad-Du'ali in the use of qias in ulus nahwi. The research method used is qualitative with a literature study as a source of data collection. Data analysis techniques include an in-depth analysis of the contributions of Ibn Mada and Abu Aswad Ad-dual in the field of Usul Nahwi and a contrast to the use of Qias Nahwi as law. The result of this research is that in the discourse on Qiyas Nahwi, the perspectives of Ibn Mada and Abu Aswad al-Du'ali present different but complementary approaches. Ibn Mada emphasized structure and precision in applying Qiyas, while Abu Asad al-Du'ali was more inclined towards context and flexibility in using this method. These two approaches enrich our understanding of how Qiyas can be applied effectively in understanding and applying the law.